2014
DOI: 10.5603/ep.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Pobudzane stosowaniem forskoliny uwalnianie wazopresyny i oksytocyny z układu podwzgórze–część nerwowa przysadki szczura in vitro jest hamowane przez melatoninę

Abstract: Introduction: Previous in vivo and in vitro studies have shown that melatonin changes vasopressin (AVP) and oxytocin (OT) secretion from the rat neurohypophysis. Additionally, melatonin is known to inhibit the forskolin-induced (forskolin is a strong adenylyl cyclase -AC activator) increase in cAMP accumulation in the rat pituitary. To determine whether the possible response of vasopressinergic and/or oxytocinergic neurones to melatonin could be mediated through a cAMP-dependent mechanism, the effect of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Oxytocin could affect increased gastrointestinal synthesis of serotonin, increased platelet serotonin uptake, or decreased serotonergic release from platelets, 14 thus, low level of oxytocin may cause a reduction in serotonin synthesis that in turn cause a decrease in the level of MT. On the other hand, another study 26 that conducted on experimental animals found that the nocturnal increase in MT may influence pituitary hormone secretion, and found that MT in physiological concentrations stimulates the release of oxytocin. This may be another explanation of the positive correlation between oxytocin and MT.…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin could affect increased gastrointestinal synthesis of serotonin, increased platelet serotonin uptake, or decreased serotonergic release from platelets, 14 thus, low level of oxytocin may cause a reduction in serotonin synthesis that in turn cause a decrease in the level of MT. On the other hand, another study 26 that conducted on experimental animals found that the nocturnal increase in MT may influence pituitary hormone secretion, and found that MT in physiological concentrations stimulates the release of oxytocin. This may be another explanation of the positive correlation between oxytocin and MT.…”
Section: Discussionmentioning
confidence: 99%
“…7 Further, melatonin inhibits the basal release of oxytocin and vasopressin at low concentration, while enhancing the secretion of these hormones at high concentrations. 8 Melatonin is known to have several functional implications on health that enable it to provide protection to cells from the effects of ionizing radiation. 9 It is also known to regulate insulin secretion, 10 sleep 11,12 and body mass.…”
Section: Introductionmentioning
confidence: 99%
“…10 -9 M) and above (10 -7 M), i.e. close to its level in the cerebrospinal fluid [18]; this observation suggests that cAMP-mediated mechanism(s) play a role in the influence of melatonin on OT and VP release.…”
Section: Introductionmentioning
confidence: 55%
“…Previous studies strongly suggest that the inhibitory impact exerted by melatonin on OT and VP secretion from the rat H-NH system engages the cAMP-mediated mechanism(s) [18]. However, although it is likely that PKA is engaged in the intracellular cAMP-mediated signalling pathway in the melatonin-dependent inhibition of neurohypophysial hormone release, this remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 96%